Sistem Informasi Manajemen Untuk Meningkatkan Kinerja Ekonomi UKM - Jaya Giri Pratama, Donny; Elisa, Nova; Nafia, Nur; Nabila, Putri; Erlin Hidayah, Rika; Ludina, Soma; Samsoni; Handayani, Aprinia (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Management Information Systems (MIS) are essential for Small and Medium Enterprises (SMEs) in the digital era to improve economic performance. MIS enables SMEs to optimize business processes, reduce operational costs, and increase productivity and competitiveness through accurate and real-time business data. SMEs are often hampered by a lack of access to timely information, which affects strategic decision-making. With MIS, SMEs gain in-depth insights into business performance, enabling more effective and efficient decision-making. However, the implementation of MIS is faced with challenges such as limited finances and technological knowledge. Support from the government and related institutions, including software subsidies and training programs, is essential to help SMEs overcome these obstacles. Proper implementation of MIS can increase operational efficiency, improve economic performance, and ensure long-term business sustainability, enabling SMEs to thrive in an increasingly digital and competitive economy.